Severe chest trauma: clinical and pathophysiological aspects - Bergalli, Luis E; Cazabán, Luis A (Cirugía del Uruguay, 1974)
The fundamental diagnostic, pathophysiological and clinical aspects of therapeutic importance in severely traumatized chest patients (T.G: T) ...